Range Management Studies, II - Performance of Cenchrus Setigerus Vahl Strains in Arid Range Land of Western Rajasthan - Sharma, S K; Verma, C M (Annals of Arid Zone, 2016)
Five strains of Cenchrus setigerus. viz .. 76, 175,296,413 and 314 were studied 5 years at a Range Management substation in the arid region of India to evaluate suitable strains for sandy range land with average annual precipitation of 335 mm. Strain Nos. 296 and 175 gave superior performance. Strain No. 296 is of spreading type and yielded maximum forage (20.2 q/ha). Strain Nos. 296 and 175 exhibited least mortality after five years of establishment and are promising strains for reseeding programme in varied arid conditions.